Uncemented total hip arthroplasty - Finlay, James (Operating Room Nurses Association of Canada Journal, 1988)
The use of uncemented prostheses in total hip arthroplasty is not a new concept; however there are new developments in the design of these prostheses. A new type of prostheses with a double layer of vitallium heading on the proximal third, uses biological anchoring through bony ingrowth rather than cement. Research suggest that once the im- plant has obtained bony ingrowth, the prosthesis/bone bond will be pennanent. Loosening will be less likely to occur compared to the cracking of cement and resorption of bone that takes place with cement.